Mewujudkan Pembelajaran Berbasis Perpustakaan Perguruan Tinggi - Khusniati Rofi'ah (IAIN Ponorogo, 2009)
Library is a source of knowledge or an information centre. its function is to collect, manage, and distribute information needed by all the academic community, especially university students who really require the library to obtain the source of information and also to complete or increase their knowledge that has been acquired from their lectures.